Consumption of monogenean eggs by crustaceans and fish. (8th December 2020) - Shirakashi, Sho; Takagi, Takuma
Abstract: The use of biological agents to control parasitic diseases in aquaculture is becoming increasingly popular as it is considered safe, effective and economically beneficial strategy for sustainable aquaculture practices. Monogeneans are among the most problematic parasites in fish farms. Their local outbreaks are largely attributed to the accumulation of eggs on farming structures, and the removal of these eggs by biological agents can be a novel solution to control monogenean diseases. We assessed the consumption of monogenean eggs by two amphipod species (a gammarid and a caprellid), the grass shrimp Palaemon pacificus and three fish (two monacanthids and Girella punctata ). The ingestion of Neobenedenia girellae and/or Heteraxine heterocerca eggs was directly or indirectly confirmed in all of the tested organisms. The eggs ingested by the crustaceans lost viability, while those eaten by fish hatched after excretion. Monacanthid filefish consumed N. girellae eggs at the highest rate, up to more than 23, 000 eggs individual ‐1 24 hr ‐1 . A cohabitation of Seriola dumerili with a monacanthid, Rudarius ercodes, showed a lower acquisition of N. girellae than those kept without R. ercodes . The results indicated that these crustaceans and fish can be useful biological agents for removing monogenean eggs from culturing facilities.